Statin use and longitudinal bone marrow lesion burden: analysis of knees without osteoarthritis from the Osteoarthritis Initiative study - Moradi, Kamyar; Mohajer, Bahram; Guermazi, Ali; Hadidchi, Roham; Mohammadi, Soheil; Cao, Xu; Wan, Mei; Roemer, Frank W.; Demehri, Shadpour (Skeletal Radiology, 2025)
Objectives: Knee subchondral bone marrow lesions (BMLs) are one of the hallmark features of structural osteoarthritis (OA) and are potential targets for statins’ disease-modifying effect. We aimed to determine the association between statin use and longitudinal changes in magnetic resonance imaging (MRI)-based BML volume in participants without radiographic knee OA at baseline. Methods: Using the Osteoarthritis Initiative (OAI) cohort, we classified participants’ knees into two categories: statin users (those who consistently used statins from baseline to the fourth year of the cohort) and non-users. We employed a 1:1 ratio propensity score (PS) matching method, adjusting for factors including age, sex, race, BMI, smoking, alcohol use, physical activity, abdominal obesity, and diabetes mellitus. We measured quantitative BML volume using a validated deep learning (DL) algorithm, applied to baseline, year-2, and year-4 intermediate-weighted fat-saturated knee MRIs. The outcome was determined by the differences in the BML volume change between statin users and non-users over the 4-year period. Results: After adjusting for potential confounders, 1502 knees were included (751 statin users and 751 non-users; mean age 63.5 ± 8.7 years, 44.5% female). A Multilevel linear mixed-effects regression model showed that statin use is associated with a smaller increase in BML volume over 4 years (time–treatment interaction effect estimates, 95% confidence interval (CI) − 14.88 mm3/year, − 23.04 to − 6.72, P < 0.001). Conclusion: In participants without baseline knee OA, continuous statin use is associated with a reduced longitudinal worsening of BML volume in the tibiofemoral joint, a known structural damage marker linked to downstream OA incidence.
CRIS-Team Scopus Importer:2025-02-17
Keywords: Bone marrow lesion; Knee osteoarthritis; Statin